2019
DOI: 10.3348/kjr.2019.0104
|View full text |Cite
|
Sign up to set email alerts
|

Altered Functional Brain Networks in Patients with Traumatic Anosmia: Resting-State Functional MRI Based on Graph Theoretical Analysis

Abstract: Objective: Traumatic anosmia is a common disorder following head injury; however, little is known regarding its neural basis and influence on the functional networks. Therefore, we aimed to investigate the functional connectivity changes in patients with traumatic anosmia compared to healthy controls using resting-state functional magnetic resonance imaging (rs-fMRI). Materials and Methods: Sixteen patients with traumatic anosmia and 12 healthy controls underwent rs-fMRI. Differences in the connectivity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…Two studies (one prospective cohort study and one retrospective case series) have investigated, using single‐photon emission computerized tomography, the migration of nasally administrated thallium. It was found that thallium migration to the OB was lower in patients with OD and correlated with olfactory threshold and OBV 1205 . Also, high thallium migration was associated with a better prognosis of olfactory recovery 1169 .…”
Section: Evaluation and Diagnosismentioning
confidence: 97%
See 1 more Smart Citation
“…Two studies (one prospective cohort study and one retrospective case series) have investigated, using single‐photon emission computerized tomography, the migration of nasally administrated thallium. It was found that thallium migration to the OB was lower in patients with OD and correlated with olfactory threshold and OBV 1205 . Also, high thallium migration was associated with a better prognosis of olfactory recovery 1169 .…”
Section: Evaluation and Diagnosismentioning
confidence: 97%
“…It was found that thallium migration to the OB was lower in patients with OD and correlated with olfactory threshold and OBV. 1205 Also, high thallium migration was associated with a better prognosis of olfactory recovery. 1169 Three other singlephoton emission computerized tomography-based studies (two prospective cohort studies and one retrospective case series) found that, after olfactory stimulation, the mean brain, frontal, temporal, and parietal perfusions were significantly lower in patients with PTOD.…”
Section: Use Of Advanced Mri Techniques For Evaluation or Management ...mentioning
confidence: 97%
“…rsFC studies also confirmed a functional impairment in OD patients. A study in patients with post-traumatic OD [ 33 ] revealed different patterns of rsFC in the olfactory network, in comparison to normosmic controls. Particularly, intra-cluster rsFC at the level of the insular cortex and anterior cingulate/frontal cortex was decreased in patients.…”
Section: Functional Mrimentioning
confidence: 99%
“…found an increase in the number of functional connections to somatosensory, olfactory, and integrative networks (i.e., regions responsible for multisensory integration) following olfactory training, mimicking those of healthy controls at baseline. Widespread networks, outside of the piriform cortex, have also been present in other task-based studies that use odor stimuli (Reichert et al, 2018;Park et al, 2019;Pellegrino et al, 2021). Reichert et al (2018) used independent component analysis (ICA) to isolate three networks active during odor stimulation.…”
Section: Pathologymentioning
confidence: 99%
“…However, using Connectome-based Predicting Modeling (CPM), a network outside of the primary olfactory cortex could discriminate between healthy and anosmic patients (with 64% accuracy) (Finn et al, 2015;Shen et al, 2017). Similarly, using resting-state data, Park et al (2019) showed that functional connectivity in traumatic olfactory loss was increased in sensory and thalamic networks in comparison to healthy controls. Additionally, those patients with worse olfaction showed an increase in global efficiency (i.e., a functional integration metric; Rubinov and Sporns, 2010) and a decrease in modularity (i.e., a functional segregation metric; Blondel et al, 2008).…”
Section: Pathologymentioning
confidence: 99%